The comfort book - Haig, Matt. (New York Penguin Life, 2021)
A small book for anyone in search of hope, looking for a path to a more meaningful life, or in need of encouragement. "Happiness occurs when you forget who you're expected to be. And what you're expected to do. Happiness is an accident of self-acceptance. It's the warm breeze you feel when you open the door to who you are." Years ago, Matt Haig began writing notes to his future self. These notes were meant as gifts to his future self: offerings of hope to help himself through anything from the darkest periods of his life to a not-so-great day. As time went on, he added new thoughts and stories, and he turned them into The Comfort Book so that everyone could draw on this well of reassurance and encouragement. Each of its short meditations gives a new perspective on life and all of its highs and lows--small islands of hope for anyone looking for a more fulfilling, more uplifting way through life. Incorporating a diverse array of sources from across the world, history, science, and his own experiences, Haig offers warmth and reassurance, reminding us to slow down and appreciate the beauty and unpredictability of existence
Keywords: Contentment